2006
DOI: 10.1111/j.1744-6570.2006.00016.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and Intraindividual Variation in Sales Outcomes: Exploring the Interactive Effects of Personality and Environmental Opportunity

Abstract: Many practices in the field of industrial‐organizational psychology assume that individual performance is stable across time; yet, little is actually known about the extent to which performance varies within individuals. We specifically address this issue by exploring the longitudinal influence of a situational opportunity (referrals received from the central office) on intraindividual performance outcomes of sales representatives. We also explore Conscientiousness and Openness to Experience as traits that exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 77 publications
3
47
1
2
Order By: Relevance
“…The study shows that ethical decision making can be infl uenced by management; education has less effect. Ethical behaviour leads to lower levels of role confl ict and higher levels of job satisfaction, but has no affect on performance ( Ramon and Munuera, 2005 ;Stewart and Nandkeolyar, 2006 ). Other studies relate personal characteristics to variations in motivation by showing that a person ' s desire for different job-related rewards (for example, pay, promotion) differ with demographic characteristics such as age, education, family size, career stage or organisational climate ( Chonko et al , 1992 ).…”
Section: Personality Factorsmentioning
confidence: 99%
“…The study shows that ethical decision making can be infl uenced by management; education has less effect. Ethical behaviour leads to lower levels of role confl ict and higher levels of job satisfaction, but has no affect on performance ( Ramon and Munuera, 2005 ;Stewart and Nandkeolyar, 2006 ). Other studies relate personal characteristics to variations in motivation by showing that a person ' s desire for different job-related rewards (for example, pay, promotion) differ with demographic characteristics such as age, education, family size, career stage or organisational climate ( Chonko et al , 1992 ).…”
Section: Personality Factorsmentioning
confidence: 99%
“…However, education may not be signifi cantly related to the behaviour and control process in the sales management. Additionally, a salesperson ' s ethical behaviour leads to lower levels of role confl ict and higher levels of job satisfaction, but not to higher performance ( Ramon and Munuera, 2005 ;Stewart and Nandkeolyar, 2006 ).…”
Section: Personality Factorsmentioning
confidence: 99%
“…Judging performance is a cognitively complex task, as raters must integrate varying levels of performance into a single judgment (Feldman, 1981;Reb & Cropanzano, 2007). One possibility is that raters average all of the employee's performance episodes exhibited over time and report this mean level performance as their overall rating (a performance episode refers to the smallest period of time in which job performance can be measured meaningfully; Stewart & Nandkeolyar, 2006). However, research has demonstrated that this is not the case.…”
Section: Positive Negative and Flat Performance Trendsmentioning
confidence: 93%
“…However, research indicates that dynamics in job performance can occur as a result of external factors, such as variation in sales referrals provided by the organization (Stewart & Nandkeolyar, 2006). While several studies have been conducted into the dynamic performance characteristics-performance rating relationship, few studies have considered the influence of individual differences on this relationship (cf.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation